Utilization of mixed anionic/cationic surfactants for styrene and ethylcyclohexane solubilization/entrapment in contaminated subsurface remediation technologies - Aranya Fuangswasdi (Chulalongkorn University, 2009)
Thesis (Ph.D.)--Chulalongkorn University, 2005